Teknik Pembenihan Ikan Kerapu Cantang (Ephinephelus sp.) di Balai Budidaya Air Payau, Situbondo, Jawa Timur - Atalla Rafilah Khalda; Shintiya Kharisma Sari; Alfina Dhea Maharani; Nadya Almira Puspitadewi; Ijl Taqiy Christya Dewantara Arthur Archiles; Prayogo Prayogo (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
Grouper fish (Epinephelus sp.) is one of the popular marine fish species in the market in Indonesia and abroad in Southeast Asia, this fish has high economic value, good taste. Currently, the development of grouper aquaculture has been growing, so the seeds must be available continuously to meet the demand for seeds, therefore the foundation of interspecies crosses between groupers that have a high heterosis effect in growth traits, disease resistance and environmental resistance. This research activity was carried out at the Brackish Water Aquaculture Center located in Situbondo, East Java and was carried out from June 19, 2023 to August 19, 2023. The working method used in the Field Work Practice is descriptive method with data collection including primary and secondary. The technique of grouper hatchery conducted at the Brackish Water Aquaculture Fisheries Center stages include tub preparation, broodstock rearing, hybridization, hatching and egg stocking, larval development, feeding, water quality management, growth sampling and grading, pests and diseases, and harvesting and marketing. The results of the observed parameters are HR 73.25%, SR 15.98%, FR 74.16%. Water quality management carried out in grouper hatcheries is water reduction and water changes according to larval age, siphon once a week and water quality tests.